TANGGUNG JAWAB ATAS KERUSAKAN BARANG YANG DIKIRIM MENGGUNAKAN EKSPEDISI - Rohi Riwu, Agustin (LPPM Universitas Doktor Husni Ingratubun Papua, 2025)
Research entitled The Responsibility of Shipping Companies for Damage to Goods is based on the development of the economy in Indonesia, especially in the increasing production of goods and services, so it is important to have a means of shipping goods to support the mobility of goods and services from one place to another. This condition is what causes the importance of the presence of shipping services. Services in the field of shipping services are closely related to responsibility. In carrying out its obligations to deliver goods, shipping companies through their ranks strive to provide the best service to users of their services. However, in reality there are still company implementations that are not in accordance with what was promised. The purpose of this study is to find out how the Shipping Company is responsible for damage to the goods being transported. The methodology in this study is an empirical method with interview techniques for the specified respondents. And the end of this study is that the agreement made between the parties refers to the provisions of Article 1320 of the Criminal Code by prioritizing the principle of freedom of contract, and the shipping party is responsible based on responsibility for the presumption, where the shipping party is obliged to prove its negligence, and if proven, it must compensate for the losses incurred. The author's contribution of suggestions is as follows: Inform the shipping service that, the service provider can also offer shipping insurance to the sender so that if damage occurs due to something, the goods can be handled